HOW CAN HUMANS DEVELOP LANGUAGE AS THEIR MEANS OF COMMUNICATION? - Muth’im, Abdul; Sutiono, Cayandrawati (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
In term of language development, humans are indeed the most capable and the most amazing creatures. They are not only able to develop their own language, their vernacular as the first language (L1), but also are able to develop other languages either as the second language (L2) or as the foreign language (FL). Many of them are not only able to communicate in one language but also in various languages. They are also able to communicate with other creatures of non-human. Even, some “selected and distinguished” humans like the prophets, for instance, are able to communicate with the Creator of all creatures, God the Almighty. The main question that needs to be answered in this study was: “How can humans develop language as their means of communication?” This question was then elaborated into: (1) How do humans develop their L1?, (2) How do humans develop their L2, and (3) How do humans develop their FL? This study employed library research method. The data were not obtained from the direct observation of primary source. Instead, they were collected from the secondary sources, such as, documents, text-books, research reports, and other relevant documented materials as the sources of data. The data collected were then analyzed and described qualitatively. The findings of the study showed that (1) humans in general are able to develop their language as the means of communication is because of the activation of the Language Acquisition Device (LAD), (2) humans develop their L1 through the process of acquisition, and (3) humans develop their L2 and FL through the process of learning, and (4) the intensity of interaction between and among language communicators contribute to the development of one’s language.